SP0171 How to select the most appropriate capillaroscopic device: pros and cons. (15th June 2017) - Ingegnoli, F
Abstract : Nailfold capillaroscopy is a simple noninvasive imaging technique mainly used to observe capillaries within the first few micrometers from the skin surface. After application of a drop of immersion oil, capillaries can be observed with a magnification lens because they run parallel to the epidermis at the nail bed area. The study of the morphology of superficial nailfold capillaries provides clinically relevant information in the management of patients with scleroderma-spectrum diseases. Recently, an international survey on non-invasive techniques to assess the microcirculation performed under the aegis of members of the European League Against Rheumatism (EULAR) Study Group on Microcirculation in Rheumatic diseases (SG_MC/RD) showed that nailfold capillaroscopy was the one most used technique in both clinical and research settings by adult physicians and paediatric rheumatologists to assess patients with Raynaud's phenomenon. A number of different instruments are available to perform the exam. They have different characteristics in terms of their cost, quality of images, magnifications, training period, portability, software for image analysis and storage. Some of these instruments can be used both in clinical and research settings such as the stereomicroscope and the videocapillaroscope. The stereomicroscope allows the widefield visualization of the nailfold with low magnifications, the training is relatively short, but the examination is difficult to perform in patients with digital flexion contractures. There appears to be consensus regarding the use of videocapillaroscopy that allows a detailed visualisation of capillary morphology using higher magnifications (100–300x). Contact probe with polarized light microscopy permits easier observation of the skin surface, and the training period is briefer. Specific softwares are available for images analysis, storage, and complete medical reports (text + images) can be produced. By contrast, in a clinical setting, nailfold capillaries can generally be visualised using more simple but also efficient tools such as a dermatoscope, USB microscope, ophtamloscope or smartphone device. The quality of images can be quite good, although the lower magnification means that some details are unlikely to be seen, and they often lack the possibility of image storage and measurement. In particular, the dermatoscope with magnification of the order of x10 is a small, inexpensive and easily portable piece of equipment that has been suggested to be comparable to videocapillaroscopy in routine clinical practice. Disclosure of Interest: None declared